1981
DOI: 10.1109/tmag.1981.1061041
|View full text |Cite
|
Sign up to set email alerts
|

The role of disorder in maximizing the upper critical field in the Nb-Sn system

Abstract: We have measured the transition temperature T , upper cr?tical field H 2(T) and the resistivity ab&e Tc , PT, , for thin fifms of electron beam co-evaporated Nb-Sn which were deposited as Nb3Sn at various substrate temperatures, or off-stoichiometry, or with tertiary additions of A1 or Zr. The T and Hc2 correlate with the resistivity, no matt& how the materials were made. A maximum H 2(0) of about 300 kOe pccurs when P ' I , 30 VR-cm and tge corresponding Tc ' I , 1 6 K; a d C Hc2 shows no sign of Pauli limiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 5 publications
3
28
1
Order By: Relevance
“…The bulk needle exhibits a 0 H c2 ͑0͒ which is comparable to the ternary wires but shows a suppressed T c ͑0͒. Orlando et al 2 have shown similar behavior in thin films with varying resistivity: Increasing the resistivity caused 0 H c2 ͑0͒ to rise, at the cost of a reduction in T c ͑0͒. Their optimal dirty film ͑ Tc =35 ⍀ cm͒ had 0 H c2 ͑0͒ = 29.5 T and T c ͑0͒ = 16.0 K at a 50% resistive criterion, compared to 26.3 T and 17.4 K for a Tc =9 ⍀ cm film.…”
Section: A Overall Behavior Of the H-t Phase Boundarymentioning
confidence: 95%
See 2 more Smart Citations
“…The bulk needle exhibits a 0 H c2 ͑0͒ which is comparable to the ternary wires but shows a suppressed T c ͑0͒. Orlando et al 2 have shown similar behavior in thin films with varying resistivity: Increasing the resistivity caused 0 H c2 ͑0͒ to rise, at the cost of a reduction in T c ͑0͒. Their optimal dirty film ͑ Tc =35 ⍀ cm͒ had 0 H c2 ͑0͒ = 29.5 T and T c ͑0͒ = 16.0 K at a 50% resistive criterion, compared to 26.3 T and 17.4 K for a Tc =9 ⍀ cm film.…”
Section: A Overall Behavior Of the H-t Phase Boundarymentioning
confidence: 95%
“…17,18,[21][22][23] Extrapolation of data measured up to 22 T indicates a zero-temperature upper critical field ͓ 0 H c2 ͑0͔͒ in thin films ranging from 26 to 29 T, depending on resistivity. 1,2 Single-and polycrystal data, measured over the complete field range, indicate either 0 H c2 ͑0͒Ϸ24.5 T for the tetragonal phase or 29 T for the cubic phase. 3,4 The limited amount of wire 0 H c2 ͑0͒ data, mostly extrapolated from 4.2 K, ranges from about 20 T up to Ͼ30 T. 17,18,[21][22][23] This large spread causes confusion as to what value is to be regarded as realistic in multifilamentary conductors and was a prime motivation for us to make a more systematic study of the influence of the inhomogeneities that are present in wires.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-level doping increases N , but the enhancements of B C2 (4.2 K) have been small, 0:3 T in NbTi doped with Ta and Hf [6], 4 T in Nb 3 Sn doped with Ti, Ta, Zr, Mo, and V [7]. Further increases in N by high-level doping depress B C2 rapidly [7,8]. Nevertheless, there are precedents for large increases in B C2 that are correlated with large increases in N .…”
mentioning
confidence: 99%
“…22) [66] and the presence of an unreacted Nb core and y can therefore n o t be deconvol uted from the slope ( dHc2/dT) a t Tc, which i s proportional to p n y . Recent work on electron beam evaporated films [33,66] and bulk samples [20,67] has indicated t h a t there should be considerable scope for improvement in the upper c r i t i c a l f i e l d . F i g u r e 23 i s taken from the work of Orlando e t al.…”
Section: Br-nb-br Sandwichmentioning
confidence: 99%